2021
DOI: 10.3390/antiox10010135
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Allosteric Modulation of alpha7-Nicotinic Cholinergic Receptors by GAT107 Increases Bacterial Lung Clearance in Hyperoxic Mice by Decreasing Oxidative Stress in Macrophages

Abstract: Supplemental oxygen therapy with supraphysiological concentrations of oxygen (hyperoxia; >21% O2) is a life-saving intervention for patients experiencing respiratory distress. However, prolonged exposure to hyperoxia can compromise bacterial clearance processes, due to oxidative stress-mediated impairment of macrophages, contributing to the increased susceptibility to pulmonary infections. This study reports that the activation of the α7 nicotinic acetylcholine receptor (α7nAChR) with the delete allosteric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…The activation of the CAIP can maintain the inflammatory homeostasis to prevent prolonged dysregulated inflammation, which can produce tissues injury, such as ALI/ARDS, systemic inflammation, sepsis, multiple organ failure and death [ 33 , 118 , 119 ]. Numerous studies have shown that activation of the CAIP can significantly tame the overproduction of proinflammatory cytokines and attenuate lung injury in mouse models of ALI/ARDS-induced by hyperoxia, pneumonia or sepsis [ 109 , [120] , [121] , [122] , [123] , [124] ].…”
Section: Neural Modulation Of Inflammatory Responses By the Cholinerg...mentioning
confidence: 99%
See 4 more Smart Citations
“…The activation of the CAIP can maintain the inflammatory homeostasis to prevent prolonged dysregulated inflammation, which can produce tissues injury, such as ALI/ARDS, systemic inflammation, sepsis, multiple organ failure and death [ 33 , 118 , 119 ]. Numerous studies have shown that activation of the CAIP can significantly tame the overproduction of proinflammatory cytokines and attenuate lung injury in mouse models of ALI/ARDS-induced by hyperoxia, pneumonia or sepsis [ 109 , [120] , [121] , [122] , [123] , [124] ].…”
Section: Neural Modulation Of Inflammatory Responses By the Cholinerg...mentioning
confidence: 99%
“…The efficacy of CAIP activation has been reported in animals and patients with inflammatory disorders. For example, the activation of the CAIP by α7nAChRs agonists can inhibit the excessive production of proinflammatory cytokines and improve clinical outcomes in animal models of sepsis and ALI/ARDS [ 109 , 115 , 121 , 123 , 142 ]. Electronic-based interventions, such as vagus nerve stimulation and electro-acupuncture points, can also decrease the levels of both proinflammatory cytokines, such as IL-4, IL-5, IL-6, IL-13, and inflammatory cell infiltration as seen in animal models of inflammatory diseases/disorders, including endotoxemia-induced ALI/sepsis [ [143] , [144] , [145] ].…”
Section: Neural Modulation Of Inflammatory Responses By the Cholinerg...mentioning
confidence: 99%
See 3 more Smart Citations